Pengaruh Kualitas Produk dan Kewajaran Harga terhadap Kepuasan Pelanggan Arj.88 Store Cabang Penatih Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to determine the effect of product quality and price fairness on customer satisfaction of ARJ.88 Store Penatih Denpasar branch. The research method used is quantitative. The research location is in Payangan Village, Marga, Tabanan. The sample used was 95 respondents. The data analysis techniques used are Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, Test t and Test F. Based on the results of the study, it was found that product quality has a significant positive effect on customer satisfaction, price fairness has a significant positive effect on customer satisfaction, and simultaneously product quality and price fairness have a significant effect on customer satisfaction. The magnitude of the influence of the independent variable on customer satisfaction was 53.2%. The suggestion in this study is that ARJ.88 Store should make quality products with attractive designs, increase product durability, by improving the quality of raw materials used and making competitive price policies